2021
DOI: 10.1007/s12072-021-10224-4
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis associated with high 14-day and 6-week rebleeding in patients after oesophageal variceal band ligation: a retrospective, multicentre, nested case–control study

Abstract: Background and Aims: The association between prognosis of variceal bleeding and portal vein thrombosis (PVT) is unclear. In this multicentre study, we determined the effect of PVT on rebleeding and mortality in patients with acute variceal bleeding (AVB) after oesophageal variceal band ligation (EVL).Methods: Cirrhotic patients with AVB who had undergone EVL were included. The patients were allocated to either the PVT group or the control cirrhotic group (CCG) based on the presence or absence of PVT. One-year … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…[16] The previous study has reported that 14-day and 6-week rebleeding rates are higher in patients with PVT than those without PVT after esophageal variceal band ligation (EVL), [17] and 17.3% of patients with acute variceal bleeding suffer from PVT. [18] In the case of PVT, the blood owing into the liver reduces, which induces intestinal edema, bacterial translocation, and liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] The previous study has reported that 14-day and 6-week rebleeding rates are higher in patients with PVT than those without PVT after esophageal variceal band ligation (EVL), [17] and 17.3% of patients with acute variceal bleeding suffer from PVT. [18] In the case of PVT, the blood owing into the liver reduces, which induces intestinal edema, bacterial translocation, and liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…High albumin levels possibly served as a protective factor for the 14-day and 6-week rebleeding risk in patients after EVL. [17] Theoretically, abundant albumin infusion in patients with GIB may cause rebleeding due to increased portal pressure in a manner similar to the liberal transfusion strategy. [27] The necessity of albumin infusion in patients without hypoproteinemia and the related dosage remains to be clari ed.…”
Section: Discussionmentioning
confidence: 99%
“…28 In our trial, we did not exclude patients with Child-Pugh grade C. Consequently, considering clinical safety, we did not plan to use NSBBs as the essential treatment for patients with Child-Pugh grade C included in this trial. Furthermore, NSBBs have been reported to increase the risk of portal vein thrombosis in patients with cirrhosis with esophagogastric varices [29][30][31] ; at the same time, out-of-hospital application of NSBBs poses a great risk for patients with poor compliance; thus, we do not choose to routinely apply NSBBs. However, if the patients need a combination of NSBBs for secondary prophylaxis, we will administer NSBBs to them.…”
Section: Discussionmentioning
confidence: 99%
“…AVB is a severe complication of liver cirrhosis, with a high rate of recurrence and death. For AVB, most adverse events (i.e., death, failure to control bleeding, and rebleeding ) occur within the rst ve days and are de ned as the 5-day failure [4]. So, it is still challenging for clinicians to initiate anticoagulation in PVT patients having cirrhosis and AVB.…”
Section: Impact On Liver Functionmentioning
confidence: 99%
“…A systematic review observed a higher rate of 5-day failure, 14-day, 6-week, and 1-year rebleeding in cirrhotic AVB patients combined with PVT [3]. Our team recently veri ed that PVT was associated with high 14-day and 6-week rebleeding among AVB patients after esophageal variceal band ligation (EVL) [4].…”
Section: Introductionmentioning
confidence: 99%